HUBUNGAN POWER OTOT TUNGKAI DAN KELENTUKAN PUNGGUNG DENGAN KETEPATAN JUMP SMASH PADA ATLET BULU TANGKIS PPLP PROVINSI RIAU - Muhamad Dalal; Saripin '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research is when the athlete jumped and the attitude while the body is in the air when do a jump smash in badminton so that the cock is easy to be returned by the opponent. The aimed of this research is to know whether the connection between leg muscle’s power and back’s flexibility with the accuracy of jump smash to the PPLP badminton athlete in Riau Province. The data interpretation tecnique is all population in PPLP Badminton of Riau Province, and the sample of this research is the PPLP Badminton athlete which consist of 9 persons. Based on the calculation of correlation between leg muscle’s power () to the accuracy of jump smash () is obtained that  while  with degree . It can be conclude that there is no significant correlation between leg muscle’s power to the accuracy of jump smash. Then the result from the calculation of correlation between back’s flexibility () with the accuracy of jump smash () is obtained that while  with degree . It can be conclude that there is a significant connection between back’s flexibility with the accuracy of jump smash. Afterwards the result from the calculation of double correlation (R test) is obtained that  while  so,  and it’s mean  there is a significant connection between leg muscle’s power () and back’s flexibility () with the accuracy of jump smash (). Key Words:    Leg Muscle’s Power, Back’s Flexibility, Accuracy of Badminton’s Jump Smash